1991
DOI: 10.1093/genetics/128.3.529
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the Coprinus cinereus mating type A factor demonstrates an unexpectedly complex structure.

Abstract: We report here the molecular cloning of the A43 mating type factor from Coprinus cinereus, a basidiomycetous fungus. Our molecular analyses revealed an unexpected source of variation in the A factor. Though genetic studies have demonstrated that A has two subunits, alpha and beta, we located three nonoverlapping fragments in the A43 region that have A factor function following DNA-mediated transformation. The three fragments demonstrate no similarity to one another as judged by restriction enzyme maps and by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1994
1994
1998
1998

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Mating system: In the dikaryon, the A locus controls the synchronized division of parental nuclei and the initiation of the clamp cell (SWIEZYNSKI and DAY 1960a). Only one gene pair in A must be different from its homologue's counterpart for sexual reproduction to proceed (MAY et al 1991;KUES et al 1992). Fully compatible matings and complete sexual development require that the two mating haploids must also differ at B, which controls clamp cell fusion and nuclear migration.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mating system: In the dikaryon, the A locus controls the synchronized division of parental nuclei and the initiation of the clamp cell (SWIEZYNSKI and DAY 1960a). Only one gene pair in A must be different from its homologue's counterpart for sexual reproduction to proceed (MAY et al 1991;KUES et al 1992). Fully compatible matings and complete sexual development require that the two mating haploids must also differ at B, which controls clamp cell fusion and nuclear migration.…”
Section: Methodsmentioning
confidence: 99%
“…These regions have been termed the alpha and beta gene clusters to correspond to DAY'S description of the locus. An allelic difference at any gene pair between two mating strains is sufficient for compatibility (MAY et al 1991;KUES et al 1992). However, a view of the A locus as having two segregating subloci conflicts with results of population genetic analyses, which have demonstrated that three subloci segregate in natural populations.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…C. cinerea strain AmutBmut (A43mut, B43mut, pab1), a self-compatible homokaryon that forms fruiting body and oidia in a light-regulated manner (Swamy et al 1984;May et al 1991;Kertesz-Chaloupková et al 1998;, was used for investigating VOCs released during life cycle development.…”
Section: Cinerea Strainmentioning
confidence: 99%
“…Da mesma forma que em S. commune, em Coprinus cinereus foram identificados no locus A (HD) dois sub loci, o sub locus A alfa e o sub locus A beta Sua organização molecular é mais conhecida devido ao fato desse sub-loci estarem muito próximos, o que permitiu o seu isolamento molecular como um todo (Mutasa et al 1990;May et al 1991;Pardo et al 1996).…”
Section: Características Do Sistema Mating Type De Coprinus Cinereusunclassified